Urinary albumin-to-creatinine ratio levels are associated with subclinical atherosclerosis and predict CVD events and all-cause deaths: a prospective analysis. Issue 3 (3rd March 2021) - Liu, Shanshan; Niu, Jingya; Wu, Shujing; Xin, Zhuojun; Zhao, Zhiyun; Xu, Min; Lu, Jieli; Wang, Tiange; Chen, Yuhong; Wang, Shuangyuan; Lin, Hong; Xu, Yiping; et al.
Abstract : Objective: We aimed to examine the associations of urinary albumin-to-creatinine ratio (ACR) levels with risks of subclinical atherosclerosis, cardiovascular events and all-cause deaths. Methods: Data from a large population-based cohort were used, which included 9580 participants aged ≥40 years free from cardiovascular diseases. Carotid intima–media thickness, brachial-ankle pulse wave velocity and ankle-brachial index were measured at baseline to assess subclinical atherosclerosis. After a median of 4.53 years' follow-up, 486 cardiovascular events and 230 all-cause deaths were recorded. Results: The urinary ACR levels were categorised into three groups. Compared with the normal group (0≤ACR <7.82 mg/g), people with low-grade albuminuria (7.82≤ACR <30 mg/g) and albuminuria (ACR ≥30 mg/g) had higher levels of subclinical atherosclerosis. In prospective analysis, people with low-grade albuminuria was not significantly associated with cardiovascular events (HR=1.18; 95% CI 0.95 to 1.46], whereas people with albuminuria had a 50% higher risk of cardiovascular events (HR=1.50; 95% CI 1.11 to 2.03). People with low-grade albuminuria and albuminuria had 43% (HR=1.43; 95% CI 1.05 to 1.93) and 87% (HR=1.87; 95% CI 1.24 to 2.81) higher risks of all-cause deaths during follow-up, respectively. In stratified analysis, the association of higher ACR with risks of cardiovascular events and all-cause deaths was stronger among individuals with concomitant subclinical atherosclerosis, the presence of diabetes and more cardiovascular risk factors, respectively. Conclusions: ACR levels were positively associated with subclinical atherosclerosis and predicted the risks of cardiovascular events and all-cause deaths. Evaluation of ACR levels should be integrated into risk stratification and prevention of cardiovascular events and all-cause deaths, especially among those with pre-existing subclinical atherosclerosis and cardiometabolic abnormalities.